Data superstream. (O'Reilly Media, Inc., 2023)
Quickly collecting, analyzing, and visualizing data to make data-driven business decisions is imperative to building an effective data strategy--and to maintaining a competitive edge for your business. We can now do analytics that reflect data in near real time, enabling better and faster insights at the point of decision. We can also process and query new data faster than ever before, running hundreds of thousands of queries per second with added layers of cutting-edge analytical capabilities. So what does this mean for your organization? The ability to unlock faster, more actionable insights for all in real time. Join us to dive deeply into the modern world of real-time analytics. Data engineers, developers, and architects will explore the latest trends in real-time analytics--including modern data applications, streaming technologies, data architecture, and tools--straight from experts and practitioners successfully putting them to use in the field.